2023
DOI: 10.1021/acssensors.2c02097
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Small Molecule Aptasensing based on Hybridization Chain Reaction and CRISPR/Cas12a Using a Portable 3D-Printed Visualizer

Abstract: Next-generation biosensing tools based on CRISPR/Cas have revolutionized the molecular detection. A number of CRISPR/Cas-based biosensors have been reported for the detection of nucleic acid targets. The establishment of efficient methods for non-nucleic acid target detection would further broaden the scope of this technique, but up to now, the concerning research is limited. In the current study, we reported a versatile biosensing platform for non-nucleic acid small-molecule detection called SMART-Cas12a (sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Moreover, the detection sensitivity was improved by combining isothermal amplification. As shown in Figure D, Ma et al reported a versatile biosensing for ATP using the HCR (hybridization chain reaction) and CRISPR/Cas . The HCR cascade signal amplification was first triggered by the target-binding functional nucleic acid (aptamer), followed by CRISPR/Cas12a recognizing the amplified products to activate trans -cleavage.…”
Section: Detection Of Non-nucleic Acid Targetsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the detection sensitivity was improved by combining isothermal amplification. As shown in Figure D, Ma et al reported a versatile biosensing for ATP using the HCR (hybridization chain reaction) and CRISPR/Cas . The HCR cascade signal amplification was first triggered by the target-binding functional nucleic acid (aptamer), followed by CRISPR/Cas12a recognizing the amplified products to activate trans -cleavage.…”
Section: Detection Of Non-nucleic Acid Targetsmentioning
confidence: 99%
“…As shown in Figure 3D, Ma et al reported a versatile biosensing for ATP using the HCR (hybridization chain reaction) and CRISPR/Cas. 24 The HCR cascade signal amplification was first triggered by the target-binding functional nucleic acid (aptamer), followed by CRISPR/Cas12a recognizing the amplified products to activate trans-cleavage. The target was converted to fluorescent signals that can be easily visualized and analyzed by using a custom 3D-printed visualizer.…”
Section: Detection Of Heavy Metal Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…have been constructed for the detection of nucleic acids and different non-nucleic acid targets, such as ions, small molecules, proteins, and pathogenic bacteria, , and detection of non-nucleic acid analytes needs an efficient means to convert targets quantification to nucleic acid analysis. For small molecule analysis, current methods mainly focus on precious designing of target-induced structure-switchable aptamer probes to regulate the activity of the CRISPR/Cas system; thus, rational engineering of the guide RNA (crRNA) and active DNA (acDNA) sequence for different targets is required. ,,,, The development of universal strategies for direct switching CRISPR/Cas systems for different small molecule detection is challenging and critical for expanding the CRISPR/Cas-based analytical application.…”
mentioning
confidence: 99%
“…For small molecule analysis, current methods mainly focus on precious designing of target-induced structure-switchable aptamer probes to regulate the activity of the CRISPR/Cas system; thus, rational engineering of the guide RNA (crRNA) and active DNA (acDNA) sequence for different targets is required. 1,12,13,16,17 The development of universal strategies for direct switching CRISPR/Cas systems for different small molecule detection is challenging and critical for expanding the CRISPR/Cas-based analytical application.…”
mentioning
confidence: 99%